INCREASE STUDENTS CREATIVITY OF ART AND PAINTING USE FINGER PAINTING TECHNIQUE - Yuseva, Risma; Panjaitan, Efrini; Sirait, Faisal (JURNAL EDUCATION AND DEVELOPMENT, 2025)
Art, especially painting, plays an important role in children's development, especially in fostering creativity, fine motor skills, and emotional growth. This study aims to explore the impact of finger painting activities on the creativity and interest of elementary school students, particularly students in grades 1 to 3. The study used qualitative methods, including observations, interviews, and practical activities with 25 students. Findings showed that the majority of students (17 out of 25) showed high interest in painting activities, associating it as a fun and self-expressive activity. On the other hand, some students (8 out of 25) showed low interest in painting, perceiving it as a dirty or boring activity. This research highlights the significant benefits of painting, including improved hand-eye coordination, increased patience, and enhanced emotional expression. In addition, the study also emphasized the challenges faced by teachers and students, such as limited time and resources in the school curriculum. The study concluded that finger painting plays an important role in developing children's creativity, emotional skills and social interaction. In addition, the study also underscores the importance of teacher and parental support in providing the necessary facilities, time and motivation for students to explore their artistic potential to the fullest.